KURIKULUM PONDOK PESANTREN MASA ISLAM DATANG - Tanjung Tanjung (Al-SAMBASY: Jurnal Kajian Pendidikan, 2024)
Islamic Religious Education (PAI) curriculum material is an integral part of curriculum development in schools and madrasas. The PAI curriculum consists of facts, concepts, principles, laws and skills which aim to develop students' potential holistically, including cognitive, aflective and psychomotor potential. The meaning of "curriculum" comes from the Greek "currere" which means running distance, which was then applied in the field of education. In Arabic, "curriculum" is defined as Manhaj, namely the clear path that humans traverse in their lives. The principles in developing the PAI curriculum include perfect linkage with religious teachings, universal objectives of curriculum material, relative balance between curriculum objectives and content, connection with students' talents, interests, abilities and needs, maintenance of students' individual diflerences, development and change, and the link between subjects, experiences, and activities in the curriculum. Thus, the development of PAI curriculum materials is an important basis for achieving the goals of quality Islamic education